Does consumption of nitrate containing beetroot juice affect indoor rowing performance in males and females? - Greisman, G.; Kloubec, J.; Kazaks, A.; Morrow, K.; Harris, C. (Current Developments in Nutrition, 2020)
Objectives: The nitrates found in beetroot juice (BR) are known to be a precursor of nitric oxide (NO). NO is a known vasodilator which allows more oxygen to travel in the blood and may improve muscle efficiency. This study aims to measure the effect of BR supplementation on performance on 500-meter row time for trained CrossFit athletes. Many past studies have analyzed the effect of BR on male athletes, this study aimed to include both males and females.